High Performance Light Water Reactor : Design and Analyses - Schulenberg, ThomasStarflinger, Jörg [Hrsg.] (KIT Scientific Publishing, 2012)
The High Performance Light Water Reactor is a nuclear reactor concept of the 4th generation which is cooled and moderated with supercritical water. The concept has been worked out by a consortium of European partners, co-funded by the European Commission. It features a once through steam cycle, a pressure vessel type reactor, and a compact containment with pressure suppression pool. The conceptual design enables to assess its feasibility, its safety features and its economic potential.